Upaya Meningkatkan Self Confidence Siswa SMK Menggunakan Pendekatan Open Ended - Fitriani Nur Salamah; Risma Amelia (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2019)
Abstract The importance of the contribution of mathematics in human activity, especially in the successors of superior generations demands more learning that fosters students' intelligence and skill during the learning process. The ability of self-confidence is very needed for students to be able to achieve skills for superior generations. Through using an open-ended approach, students are expected to grow diverse ideas and mathematical ways of thinking so students are accustomed to completing various solutions or strategies. This study is a Classroom Action Research (CAR). The subjects in this study were students of class X RPL B in one of the CIMahi City SMKS. Based on the results of data analysis in cycle II student activity increased from each indicator 1) Belief in self-ability ability 61.81% 2) Acting independently in making decisions 67.92% 3) Having positive self concepts 69.89% and 4) Courageous expressing opinions 70.38% with the results achieved can be expressed that the ability of self-confidence increases in learning using the open-ended approach. Keywords: Self-Confidence, Open Ended Approach